Degradation Of Dyes (Methylene Blue) Using Natural Rubber Incorporated With Silver Nanoparticles In Water Treatment Tank - Khudria, Nur Atiqah Mohamad (Universiti Sains Malaysia, 2017)
Wastewater from textile industries commonly produce large amount of water often rich in colour containing residues of dyes and toxicity. In order to degrade dyes from the effluent before releasing to the environment, the natural rubber incorporated with silver nanoparticles (NR-Ag) were studied. In this work, the dye that used as a model of dye was methylene blue (M) and the NR-Ag ball membranes have been prepared using fishing float ball coated with NR-Ag. The NR-Ag ball membranes were formed using mild heat treatments and characterized using UV-Vis Spectrophotometer and Atomic Absorption Spectroscopy (AAS). Catalytic activity of the NR-Ag ball membranes for the degradation of MB dye was studies using potassium borohydride (KBH4) as reducing agent. The report emphasizes the effect of quantity of NR-Ag balls, the effect of air pressure and the effect of KBH4 concentration on decolourization rate of MB by KBH4. The rate of decolourization was found to increase with increasing amount of NR-Ag balls and with increasing of air pressure. The optimum amount of NR-Ag ball was 10 and the best air pressure rate was 0.6 bar. Furthermore, the process of decolourization increased with higher concentration of KBH4.